2007
DOI: 10.1038/sj.bjc.6603662
|View full text |Cite
|
Sign up to set email alerts
|

The research priorities of patients attending UK cancer treatment centres: findings from a modified nominal group study

Abstract: Members of the public are increasingly consulted over health care and research priorities. Patient involvement in determining cancer research priorities, however, has remained underdeveloped. This paper presents the findings of the first consultation to be conducted with UK cancer patients concerning research priorities. The study adopted a participatory approach using a collaborative model that sought joint ownership of the study with people affected by cancer. An exploratory, qualitative approach was used. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
153
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(158 citation statements)
references
References 24 publications
3
153
0
2
Order By: Relevance
“…The apparent absence of mortality in research priorities has also been observed in other areas of medicine, including cancer, mental health, and pulmonary disease, for which patients/caregivers emphasize living with and managing the illness rather than dying from it. 5,28,29 We speculate that this may also reflect a perception that mortality may not be a realistic outcome, particularly in dialysis, given that mortality rates remain unacceptably high despite advances in dialysis technologies and pharmacology. [30][31][32] Comparison With Other Research Priority-Setting Initiatives Some of the research priorities generated in this workshop reflect priority areas that are consistent with findings from a recent systematic review of research priority-setting activities in kidney disease.…”
Section: Discussionmentioning
confidence: 99%
“…The apparent absence of mortality in research priorities has also been observed in other areas of medicine, including cancer, mental health, and pulmonary disease, for which patients/caregivers emphasize living with and managing the illness rather than dying from it. 5,28,29 We speculate that this may also reflect a perception that mortality may not be a realistic outcome, particularly in dialysis, given that mortality rates remain unacceptably high despite advances in dialysis technologies and pharmacology. [30][31][32] Comparison With Other Research Priority-Setting Initiatives Some of the research priorities generated in this workshop reflect priority areas that are consistent with findings from a recent systematic review of research priority-setting activities in kidney disease.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of cancer on different aspects of life including the psychological and social consequences has been identified as top research priority among persons living with cancer [2]. The social consequences of the illness or the disease can also be referred to as sickness.…”
Section: Introductionmentioning
confidence: 99%
“…To facilitate this process, Federal Drug Administration (FDA) and European Organization for Research and Treatment of Cancer (EORTC) guidelines have made inclusion of while research on treatment and toxicity were given a much lower priority [22,23]. PROMs become even more relevant in elderly patients [24,25], as the limited disease-centered evidence for this age group shows inferior results for survival and toxicity compared to younger patients.…”
Section: Discussionmentioning
confidence: 99%